ANTIBACTERIAL ACTIVITY TEST CAUSES INFECTIONS ON THE SKIN FROM THE ENDOPHYTIC FUNGI OF BASIL LEAVES (Ocimum sanctum L.) - Uswatun Hasanah; Ahmad Shafwan S Pulungan; Endang Sulistyarini Gultom (JBIO: jurnal biosains (the journal of biosciences), 2021)
The aim of this study was to fund isolates of endophytic fungi from basil leaves (Ocimum sanctum L) which had inhibition against the growth of Staphylococcus aureus, Staphylococcus epidermidis dan Streptococcus pyogenes bacteria. The specific target to be achieved from this research is the inhibition of each isolate of the basil leaf endophytic fungus (Ocimum sanctum L) against Staphylococcus aureus, Staphylococcus epidermidis dan Streptococcus pyogenes.This study produced 26 isolates of endophytic fungi from basil leaves (Ocimum sanctum L), two (2) which has inhibitory power against Staphylococcus aureus, Staphylococcus epidermidis dan Streptococcus pyogenes bacteria.